FPGA implementation of RDMA for ATLAS readout with FELIX at high luminosity LHC. (1st May 2022) - Vasile, M.; Martoiu, S.; Boukadida, N.; Antonescu, M.; Ulmamei, A.; Stoicea, G.; Hobincu, R.; Iordache, C.; ,
Abstract: The FELIX system is used as an interface between front-end electronics and commodity hardware in the server farm. FELIX is using RDMA through RoCE to transmit data from its host servers to the software readout driver using off-the-shelf networking equipment. RDMA communication is implemented using software on both end of the links. Exploring opportunities to improve data throughput as part of the high luminosity LHC upgrade, an implementation for RDMA support in the front-end FELIX FPGA is being developed. We present a proof-of-concept RDMA FPGA implementation, which will help inform the design of the FELIX platform for high luminosity LHC.